Fabrication and characterization of {110}-oriented Pb(Zr, Ti)O3 thin films on Pt/SiO2/Si substrates using PdO//Pd buffer layer. (19th September 2017) - Oshima, Naoya; Uchiyama, Kiyoshi; Ehara, Yoshitaka; Oikawa, Takahiro; Ichinose, Daichi; Tanaka, Hiroki; Sato, Tomoya; Uchida, Hiroshi; Funakubo, Hiroshi
Abstract: A strongly {110}-oriented perovskite-type thin film of tetragonal Pb(Zr0.4 Ti0.6 )O3 (PZT) was successfully obtained on a (100)Si substrate using a {101}PdO//{111}Pd thin film as a buffer layer. The {101}PdO//{111}Pd thin film buffer layer was obtained by oxidizing {111}Pd after depositing {111}Pd on a {111}Pt/TiO x /SiO2 /{100}Si substrate. Using this buffer layer, a {110} c -oriented SrRuO3 (SRO) thin film was deposited by sputtering as a bottom electrode of PZT thin films. Subsequently, the {110}-oriented PZT thin film can be deposited on a (110) c SRO thin film by metal–organic chemical deposition (MOCVD) and its properties can be compared with those of PZT thin films with other orientations of {100} and {111}. Among the {100}, {110}, {111}-oriented PZT films, the {100}-oriented one showed the largest remnant polarization, which is in good agreement with those of the PZTs epitaxially grown in the ⟨100⟩, ⟨110⟩, and ⟨111⟩ directions. The other properties, i.e., piezoelectricity and dielectric constants, also showed similar anisotropic tendencies, which is in good agreement with the data reported in the epitaxially grown PZTs.